ANALISIS PENGARUH PENAMBAHAN UNSUR MAGNESIUM TERHADAP KUAT LENGKUNG PADA MATERIAL ALUMINIUM - farhan, farhan ikbar; Rasid, Muhammad; Sundari, Ella (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The brake handle is one of the components to restrain the vehicle's movement rate by holding the clamp mechanism, the problem that exists in the brake handle when there is a hard impact. Handles are usually made with aluminum metal material, so that aluminum has certain properties in this study combined with magnesium elements with variations of 1%, 3%, and 5%. Magnesium is the lightest chemical element among other industrial metals. The low density value and strength of magnesium is an advantage of this element as an alloy. The alloy used is a metal casting process using the sand casting method. After combining aluminum and magnesium in a bending test to get an acceptable bending strength. The percentage value of magnesium has a significant effect with a comparison of Fcount > Ftable value 72.29 > f0.0001(2;9) = 4.26. The percentage factor obtained is 87% and the maximum value is 38.08 kg/mm2 and the minimum value is 30.46 kg/mm2.